Forest Service experiences understanding power and working collaboratively: bridging the theory and practice - Williams, Peter, speaker (Colorado State University. Libraries, 2012)
Power is linked inextricably with collaborative conservation; how you handle those linkages reflects ethics in fundamental ways. These two premises underpin how many in the US Forest Service are approaching collaboration as part of public land management in the US. They also underpin work conducted on behalf of the agency's International Programs efforts in other countries. This talk will explore power and ethics broadly understood and as that understanding applies to Forest Service work to grow collaborative capacity inside and outside the agency.
Presented at the Fall 2012 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Power and Ethics in (Collaborative) Conservation", October 9, 2012, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Dr. Peter Williams is the Collaborative Planning and Multiparty Monitoring Specialist for the US Forest Service's Ecosystem Management Staff, which is part of the Washington Office. Based in Ft. Collins, Peter works throughout the country to help design collaborative planning efforts, develop agency policy related to collaborative efforts, and to bridge theory and practice. He is co-leading the agency's effort to Empower Collaborative Stewardship and serves on the Core Team of an effort to establish a National Inventory, Monitoring, and Assessment Strategy for the Forest Service. He also is involved in Large Landscape Conservation efforts, including applying ideas associated with communities of practice and broader use of electronic tools to support collaborative public land management. Peter has served as Forest Supervisor for the Wayne National Forest in Ohio, Natural Resource Staff Officer for the Colville National Forest in Washington state, and as a Research Social Scientist, among other positions. Prior to his work with the Forest Service, Peter worked as a Wilderness Workskills Instructor for the Student Conservation Association and Assistant Trails Program Director for the Appalachian Mountain Club in New Hampshire. He holds an BA from Kenyon College, an MS from Virginia Tech, and a PhD from Utah State University.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: rural and urban forests; stewardship; public land management; collaboration; research; protection